Transvaginal Ultrasound Versus Bishop Score in Predicting Labour Dystocia at Full-Term Nullipara Undergoing Labour Induction - Osama Deif; Mohammed El Messalami; Yasser Diab (Tehran University of Medical Sciences, 2024)
Objective: Precise assessment of cervical conditions before labor induction is crucial for predicting the success of normal vaginal delivery. The cervix primary condition has a significant value in determining the succession of induction of labour. Traditionally, assessment of cervix before induction has been based on a cervix digital examination using Bishop's scoring method.This study compares transvaginal ultrasonographic (TVS) cervical assessment with the traditional Bishop score in nulliparous women undergoing labor induction, aiming to evaluate their predictive abilities for labor dystocia. Materials and methods: In a prospective observational study of 200 pregnant women at Al Hussein University Hospital between October 2022 and July 2023, cervical length, funneling, and posterior cervical angle were measured using transvaginal ultrasound. The Bishop score was recorded before induction. Statistical analyses, including Student's "t"-test and ROC curve, were conducted using SPSS. Results: 68% delivered via normal vaginal delivery (NVD) and 32% via cesarean section (CS). The NVD group exhibited significantly higher Bishop scores (6.82±1.36 vs 3.70±0.94), lower cervical length (25.46±3.99 vs 37.34±2.09),and higher cervical angle (121.39±5.70 vs 89.01±6.09), than the CS group. ROC curve analysis revealed that a Bishop score ≥4.5 had 89% sensitivity and 87.5% specificity, a cervical angle ≥ 92.5 had 98.5% sensitivity and 95.3% specificity, and a cervical length ≥31.5 had 96.9% sensitivity and 97.1% specificity for predicting NVD. Conclusion: The posterior cervical angle, alongside cervical length, proves to be a more sensitive indicator for predicting labor dystocia during induction compared to the traditional Bishop score.